2003
DOI: 10.1063/1.1606529
|View full text |Cite
|
Sign up to set email alerts
|

Sample mounting and transfer mechanism for in situ IR-visible sum frequency generation vibrational spectroscopy in high-pressure ultrahigh vacuum system

Abstract: We developed a sample mounting and transfer mechanism for studying heterogeneous catalytic reactions in a high-pressure ultrahigh vacuum system. The system is optimized for the use of sum frequency generation vibrational spectroscopy to probe surface species in situ during the reactions. The system allows wide-ranging working conditions: a pressure range between 4×10−10 and 760 Torr and a temperature range between 200 and 1200 K. Rigid and reproducible sample positioning as well as precise temperature control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…This was necessary because gas molecules in the HP cell absorb some of the incoming radiation. Detailed descriptions on the HP/UHV system and SFG measurement can be found elsewhere [18,19].…”
Section: Sum Frequency Generation Vibrational Spectroscopymentioning
confidence: 99%
“…This was necessary because gas molecules in the HP cell absorb some of the incoming radiation. Detailed descriptions on the HP/UHV system and SFG measurement can be found elsewhere [18,19].…”
Section: Sum Frequency Generation Vibrational Spectroscopymentioning
confidence: 99%
“…In addition, the intensities of both types of polarized photons are dependent on gas-phase absorption, which means that the reflection of s-polarized light exclusively yields gas-phase information, while the difference in reflection between p-and s-polarized light contains surfacespecific information. Several systems have been realized that attach a high-pressure cell for PM IRRAS 28 or for SFG spectroscopy 29,30 to a UHV chamber. Polarized light is also used in ellipsometry and related techniques, such as ellipso-microscopy for surface imaging (EMSI) [31][32][33] and reflection anisotropy microscopy (RAM).…”
Section: Surface Characterization At High Pressurementioning
confidence: 99%
“…The signal-to-noise ratio was further enhanced by a gated integrator, while the IR beam was scanned through the spectral region of interest. Additional information about the SFGVS system used in this study can be found elsewhere. …”
Section: Methodsmentioning
confidence: 99%